Falls in Turkish Women During Pregnancy: Prevalence, Affecting Factors and Treatment-seeking Behavior - Özlem Aşcı; Semra Kocaoz; Pınar Kara; Ferdane Taş (Mashhad University of Medical Sciences, 2021)
Background & aim: Physiological, anatomical and hormonal changes that occur during pregnancy could increase pregnant women's risk of falling, which could lead to negative outcomes for both women and fetuses. This study aims was to identify the prevalence and influencing factors of falls in Turkish women during pregnancy as well as these women's treatment-seeking behavior. Methods: This retrospective and descriptive study was conducted with 622 pregnant women who presented for prenatal follow-up at Niğde Training and Research Hospital in Turkey using the convenience sampling method. The data were collected with the "Structured Questionnaire Form" and "Trait Anxiety Inventory", and analyzed using SPSS 24.0 software using descriptive statistics, Chi-squared and Student's t-tests and logistic regression analysis. Results: The prevalence of falls in pregnant women at term was found as 17.7%. The falls most commonly occurred at home (62.3%), on stairs (16.8%), and on wet (16.8%) or uneven ground (13.9%). The rates of injury and going to a hospital after such a fall were 63.6% and 14.2%, respectively. Trait anxiety mean scores did not show a significant difference in terms of pregnancy fall history (p>0.05).Regression analysis revealed a significant relationship between a fall history during pregnancy and medication use (OR=1.680; p=0.025) and clothing style (OR=1.836; p=0.025). Conclusion: Approximately two out of ten pregnant women have a history of falling, with the falls usually being associated with preventable causes. It is recommended that pregnant women be informed by midwives and other healthcare professionals about falls, avoiding risk factors and seeking medical treatment.